Evaluation of The Performance of Incubation Business Services in Morocco - Kenza Bouarara; Mohamed Oudgou; Abdelilah Baguare (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
The purpose of this article is to make an empirical assessment of the services offered by the incubation structures in Morocco. To do this, we will focus on the identification of the incubation actors and the services offered by these structures. Within this framework, two studies are envisaged: the first one aims at exploring entrepreneurial incubation as it is conceived and seen by its practitioners, and a confirmatory method that will focus on the perception of this practice on the part of "incubated or clients of incubators". The results are complementary and indicate a gap between the image of incubation and its reality. This has helped us to formulate recommendations to bring our judgment on this practice.